Effects of MiR-214-3p Regulation of SERCA2a Expression on Contractility of Cardiomyocytes in Heart Failure Model: MiR-214-3p Regulation and Heart Failure Model - Hu, Tianming; Liu, Lan (Cellular and Molecular Biology, 2022)
This study aimed to explore the targeted regulation of microRNA-214-3p (miR-214-3p) on sarcoplasmic/endoplasmic reticulum Ca(2+)-ATPase 2a (SERCA2a) and its mechanism on heart failure (HF). In this study, a rat model of HF was established by injecting isoproterenol to detect the changes in heart function. Then the primary rat cardiomyocytes were extracted and cultured. The cells were divided into the normal group, HF model group, miR-214-3p mimic group, and inhibitor group according to treatment methods. The expression differences of SERCA2a in each group were detected. The binding sites of miR-214-3p and SERCA2a were predicted, wild-type or mutant SERCA2a was prepared and co-transfected into cardiomyocytes with mimic, and the targeting effect was detected by the dual-luciferase reporter gene. Finally, the systolic function of each group was detected by a single-cell systolic dynamic edge detection system. The results showed that cardiac output and left ventricular ejection fraction of HF rats were significantly lower than those of normal rats (P<0.05). The results of the cell test showed that messenger ribonucleic acid (mRNA) and protein expression levels of SERCA2a in the model group and the mimic group were significantly lower than those in the mimic group (P<0.05), but there were no differences between normal group and inhibitor group (P>0.05). Target prediction revealed that miR-214-3p had a complementary pairing of 6 bases with the SERCA2a 3’non-coding region. After co-transfection with miR-214-3p mimic and wild-type SERCA2a expression vector, the dual-luciferase activity was significantly decreased (P<0.05). The percentage of maximal contraction amplitude, peak contraction time, and 50% diastolic time of cells in the model group and mimic group decreased significantly. The mimic group was significantly smaller (P<0.05), but there were no differences between the normal group and the inhibitor group (P>0.05). These results indicated that SERCA2a expression was significantly reduced in HF cells, and miR-214-3p could inhibit SERCA2a expression by targeting the SERCA2a 3’UTR region. Inhibition of miR-214-3p could promote the expression of SERCA2a, which in turn promoted the contractile function of HF rat cardiomyocytes.